Primary Sjögren’s Syndrome - A Review - Pittala, Vyshnavi; Mallannagari, Shivanjali; Sherla, Harika; Kadarla, Rohith Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Primary Sjögren’s syndrome is a systemic autoimmune disease. The hallmark of the disease is exocrinopathy, which often results in dryness of the mouth and eyes, fatigue, and joint pain. These three symptoms are present in more than 80% of the patients with this disease and have a major effect on quality of life, primarily because of disabling fatigue, with associated loss of work productivityThe global prevalence calculated for the rarer pSS is 61 per 100 000 inhabitants. The patients’ quality of life is reduced by the diverse manifestations of the disease. Pharmacists can help SjS(Sjögren’s Syndrome) patients improve their quality of life.